PEMBERDAYAAN ZAKAT DALAM MENGENTASKAN KEMISKINAN - Siti Aminah Chaniago (Jurnal Hukum Islam, 2015)
Zakat must be spent rich man that aims to reduce poverty. There are some obstacles in gathering the zakat, awareness among the obligatory zakat, facilities, inadequate management of amil and policies that strengthen the rule shar'i not adequate. Likewise sanctions given to the muzaqis directly who do not pay the zakat is not available. These errors must be resolved based on previous experiences, if not the eradication of poverty through the empowerment charity will not be complete. All aspects and institutions should be synergy to solve the problems. Government as regislator and facilitator should be control the activities.